Qualidade de vida relacionada à saúde em indivíduos curados de tuberculose pulmonar: uma revisão de escopo - Alves, Klink Ramos (Brasil, 2023)
Pulmonary tuberculosis (PTB) adversely affects psychological and physical well-being, so that months after a person is considered cured of the disease, it is still possible to find changes in health-related quality of life (HRQoL). The objective was to summarize the scientific evidence in order to identify the types of HRQoL measurement instruments that are available for individuals cured of PTB. This study is a scoping review developed using the JBI Collaboration methodology and reported following the PRISMA-ScR. Studies carried out with participants cured of PTB aged ≥18 years, who assessed HRQoL regardless of the measurement instrument used, carried out in any geographic, socioeconomic and clinical context, published and unpublished, without time or language restriction were considered. The search strategy considered published and unpublished studies through the information sources CINAHL, EMBASE, LILACS (via VHL), MEDLINE (via PubMed), PEDro, SciELO, Scopus, Web of Science, Cybertesis, NDLTD and Google Scholar. Studies were selected on the Rayyan platform by two independent reviewers. Data were extracted using a data extraction form prepared by the reviewers themselves. Twelve studies were selected from 1644 records initially found, with a total of 2307 participants and age range from 25 to 70 years. In conclusion, the most used HRQoL measurement instrument was the Saint George Respiratory Questionnaire (SGRQ), with the percentage of HRQoL change after PTB between 18 and 86%.